Influence of geopolitical changes on the Formation of Master's Programs in Sports Journalism in student training - Bojkova, Nina; Berdysheva, Natalia; Kalashnikova, Elena; Murtazina, Gulsina; Karazhaeva, Madina (Revista Conrado, 2023)
The article analyzes the relationship between geopolitical problems and the development of training programs for students specializing in sports journalism. The study problem is that education is aimed at training highly specialized specialists who do not consider sports issues in the context of international, political, and socio-psychological problems of modern society. Specialized sports media do not pay enough attention to the socio-political problems in sports discourse that occur all over the world. The authors conduct a comparative analysis of the Internet and network media. In the course of the study, it is determined that 70% of modern Russian media are represented by an insider view of sports topics. The authors conclude that when teaching journalism, sports topics should be considered not only from a sports point of view but also from political, ideological, economic, and social aspects. Keywords: Student Training, Formation of Educational Programs, Sports Journalism, Analytical Discourse, Author Journalism. RESUMEN El artículo analiza la relación entre los problemas geopolíticos y el desarrollo de programas de formación para estudiantes de la especialidad de periodismo deportivo. El problema de estudio es que la educación está dirigida a formar especialistas altamente especializados que no consideran los temas deportivos en el contexto de los problemas internacionales, políticos y sociopsicológicos de la sociedad moderna. Los medios deportivos especializados no prestan suficiente atención a los problemas sociopolíticos del discurso deportivo que se dan en todo el mundo. Los autores realizan un análisis comparativo de Internet y los medios de red. En el curso del estudio, se determina que el 70% de los medios rusos modernos están representados por una visión interna de los temas deportivos. Los autores concluyen que en la enseñanza del periodismo se deben considerar los temas deportivos no solo desde el punto de vista deportivo sino también desde los aspectos: político, ideológico, económico y social. Palabras clave: Formación de Estudiantes, Formación de Programas Educativos, Periodismo deportivo, Discurso Analítico, Periodismo de autor